2015
DOI: 10.1094/pdis-06-14-0633-re
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Sensitivity of Pyraclostrobin and Toxicity of SHAM to Sclerotinia sclerotiorum

Abstract: Sclerotinia sclerotiorum is a cosmopolitan plant pathogen notable for its wide host range. The quinone outside inhibitor (QoI) fungicide pyraclostrobin has not been registered for control of S. sclerotiorum in China. In this study, baseline sensitivity of pyraclostrobin was established based on effective concentration for 50% inhibition of mycelial growth (EC50) values of 153 isolates of S. sclerotiorum collected from five provinces of China and toxicity of alternative oxidase inhibitor salicylhydroxamic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 23 publications
0
12
0
2
Order By: Relevance
“…SHAM is a relatively poor inhibitor of the AOX, with an inhibition constant ( K i ) of 21 μ m against the Trypanosoma brucei enzyme (as measured by glycerophosphate‐linked oxygen uptake assay) [81]. As an antifungal agent, SHAM has also been observed to act synergistically with QoIs in vitro , but this response is species (and QoI)‐dependent [65,70,82]. Unfortunately, SHAM is a relatively nonspecific inhibitor and poorly taken up by plants, and so is unsuitable for use in the field [70].…”
Section: Alternative Qoi/qii Resistance Mechanisms In Fungal Phytopatmentioning
confidence: 99%
“…SHAM is a relatively poor inhibitor of the AOX, with an inhibition constant ( K i ) of 21 μ m against the Trypanosoma brucei enzyme (as measured by glycerophosphate‐linked oxygen uptake assay) [81]. As an antifungal agent, SHAM has also been observed to act synergistically with QoIs in vitro , but this response is species (and QoI)‐dependent [65,70,82]. Unfortunately, SHAM is a relatively nonspecific inhibitor and poorly taken up by plants, and so is unsuitable for use in the field [70].…”
Section: Alternative Qoi/qii Resistance Mechanisms In Fungal Phytopatmentioning
confidence: 99%
“…However, the use of SHAM in vitro is controversial. In fact, it was shown that in some pathogens AOX is active also in planta , therefore questioning the use of SHAM in vitro to suppress AOX, as it could lead to overestimation of QoI activity 24 . Moreover, inhibitory effect of SHAM on the growth of some fungal pathogens was observed 25,26 , and therefore we evaluated the effect of novel dual compounds and commercial fungicides without the addition of SHAM.…”
Section: Resultsmentioning
confidence: 99%
“…These results were possible because metalaxyl belongs to the phenylamides group, which inhibits the synthesis of ribonucleic acid (RNA), affecting mycelial growth, spore formation and pathogen infection (Fishel and Dewdney, 2012). Liang et al (2015) evaluated the effect of pyraclostrobin on Sclerotinia sclerotiorum , and reported that close to 100% inhibition was obtained when using salycilhydroxamic acid. Without the latter, the inhibition was significantly reduced.…”
Section: Resultsmentioning
confidence: 99%